Optimalisasi Nutrisi Ibu Hamil: Strategi Preventif Untuk Mencegah Stunting Pada Anak: Sebuah Program Pengabdian Kepada Masyarakat Di Kabupaten Bulukumba - erniawati, erniawati; Sumarni; Jumriani; Ariani; Husnul Khatima (JCS, 2024)
ABSTRACT Stunting is a nutritional problem that has long-term impacts on children. Research shows that proper nutrition during pregnancy can prevent stunting. This community service activity aims to educate pregnant women about the importance of adequate nutritional intake. The program is targeted at mothers with stunted children. This initiative employs educational methods and the distribution of eggs as a direct application to the community. The activity will be held in October 2024. The target group includes mothers with stunted children located in Ujung Bulu District, Bulukumba Regency, specifically in Bintarore, Tanah Konkong, Kasimpureng, and Ela-Ela Villages. This community service effort not only contributes to increasing knowledge but also promotes long-term health for future generations. Keywords: Nutrition, Pregnant Women, Stunting, Education